Assessment of the impacts of climate change on cold region pavement design and operation - Yusheng Jiang; Shafi Ullah; Claudia Zapata; Xiong Yu (Journal of Infrastructure Preservation and Resilience)
Abstract Cold region pavements are subjected to climate impacts, as frost heave and thaw settlement can significantly deteriorate the pavement surface conditions and reduce its service life. Due to the freezing/thawing behaviors, the smoothness of the flexible pavement surface usually shows seasonal fluctuations, i.e., an increases or decreases of international roughness index (IRI) during freezing season or thawing season, respectively. However, few existing models capture such season-dependent mode of IRI variations. In this study, calibrated models for flexible pavement are proposed for evaluating the IRI on seasonal scales through both global and local calibrations. The globally calibrated model successfully links the freezing–thawing processes to flexible pavement performance. The performance of both the global and local calibrations are verified by field measurements at selected road sections and Mechanistic Empirical Pavement Design Guide (MEPDG) model predictions. The proposed model connects climatic factors with pavement performance, and therefore offering a tool to assess the pavement IRI response to future climate changes. Based on the globally calibrated model, a series of analyses were conducted to forecast the impacts of climate change on IRI at sites located in different cold climate zones. The effects of climate change on pavement construction and operation are investigated. From this, the impacts of climate change on pavement design adaptation as well as the environmental footprint of vehicle operations are estimated.